Atomic layer deposition of photoelectrocatalytic material on 3D-printed nanocarbon structures - Ng, Siowwoon; Zazpe, Raul; Rodriguez Pereira, Jhonatan; Michalicka, Jan; Macák, Jan; Pumera, Martin (Royal Society of Chemistry, 2021)
3D-printing is an excellent tool for the prototyping and fabrication of a variety of devices. The ability to rapidly create on demand structures opens the vast possibilities for the innovations in catalysis and energy conversion/storage devices. The major bottleneck is that the materials which are suitable for 3D-printing usually do not possess the required energy conversion/storage ability. Atomic layer deposition (ALD) strategically offers homogeneous and conformal deposition of functional layers without compromising the 3D topography. Here, we show that readily fabricated fused deposition modeling extruded nanocarbon/polylactic acid (PLA) electrodes can be modified by a photoelectrocatalytic material with atomic precision. We use an archetypal material, MoS2, with high electrocatalytic hydrogen evolution reaction (HER) activity, whilst possesses high photons absorption in the visible spectral region. We optimized the ALD process at low temperature to coat 3D-printed nanocarbon/PLA electrodes with different number of MoS2 ALD cycles for photoelectrocatalytic HER. We present for the first time, the feasibility of low temperature transition metal dichalcogenide coatings on 3D-printed nanocarbon surface, unequivocally elevate the benchmark of functional coatings by ALD on any 3D-printed platforms.
Depozice atomárních vrstev fotoelektrokatalytického materiálu na 3D tištěné uhlíkové nanostruktury.
Keywords: 3D printing; filament; nanocarbon; Atomic layer deposition; MoS2; 3D tisk; filament; nanouhlík; depozice atomárních vrstev; MoS2